Application of Moderation Value on Legal Attitudes to Transact with Conventional Banks - Hidayat Darussalam (Istinbath : Jurnal Hukum, 2024)
This article aims to analyse the legal attitude of the community towards conventional bank interest and the application of this legal attitude in society. Islam forbids all forms of transaction applications of buying and selling or lending with usury systems. However, the mechanisms and systems of modern banking transactions are not yet known comprehensively in Islam and give rise to differences of opinion among Muslims. This difference of opinion is inseparable from their paradigm of thinking, namely textual and contextual ways of thinking. This case can be categorised as a matter of ijtihâdiyyah khilâfiyyah. This difference of opinion is very likely to occur because the rules of muamalah matters are actually allowed in sharia and become haram (forbidden) until there is evidence that prohibits it. Problems arise when the understanding that is believed to be related to sharia economic law, so that it feels that its understanding is the absolutely correct understanding, and then considers it a mistake if there are other people's opinions differ from it. The emergence of intolerant polemics like this can spark the fire of discord and cause distorted perceptions in the community related to religious harmony.  Using a sociological approach, this article analyses the legal attitude towards conventional banks and its application in social life. The results of the study show that moderation is needed in viewing differences in legal attitudes related to bank interest so as to present a tolerant dogmatism of society and be able to avoid divisions due to intolerant attitudes.